TEACHING HYDROGEN BONDING : A NEW APPROACH - Aggarwal, I.P. (SCHOOL SCIENCE, 2012)
While dealing with school science teaching, sometimes we are placed in a very embarrassing position because we do not have any model or demonstration to make the lesson interesting. Under these circumstances we should try to correlate teaching with environment. In this article an attempt has been made to motivate teachers of chemistry to teach hydrogen bonding at the +2 level through environment.